An Analytic Survey On Current Clustering Technique of data Categorizing and Retrieving (International Journal of Engineering and Computer Science, 2017)
in this survey we have a furnished detail of Clustering. Clustering is not only bounded in boundary of grouping of same kind of objects in cluster, it would also be like to get or retrieve specific data by just analyzing clustering approach. This analytic survey focused on the current clustering technique of data categorizing and retrieving as faster as possible from huge amount of data because data is growing like square or cube of their current position. So saving of all information and easier retrieving will always face new challenges as proportion of data increasing in various aspects which would population of any country or data of any field related to them